Magnetic powder and granules, method for manufacturing magnetic powder and granules, and method for manufacturing rare earth magnets

JP2026166842APending Publication Date: 2026-10-14HONDA MOTOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025060056
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0016】 以上の態様によれば、過電流損失が低減された希土類磁石の材料となる磁性粉粒体、磁性粉粒体の製造方法、及び、磁性粉粒体から希土類磁石を製造する希土類磁石の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166842000001_ABST
    Figure 2026166842000001_ABST
Patent Text Reader

Abstract

To provide magnetic powders and granules that can be used as materials for rare earth magnets with reduced overcurrent loss, a method for manufacturing magnetic powders and granules that facilitates the production of magnetic powders and granules, and a method for manufacturing rare earth magnets with reduced overcurrent loss from magnetic powders and granules. [Solution] The magnetic powder granules 6 contain stacked, flaky rare earth magnetic powder 7, the thickness of the magnetic powder granules 2 is 0.15 mm or more, the lower limit of the major axis of the rare earth magnetic powder 7 is 300 μm, and the average thickness of the rare earth magnetic powder 7 is 10 μm to 30 μm. The method for manufacturing the magnetic powder granules 6 includes a (B) binding step in which the rare earth magnetic powder 7 is bound to obtain the magnetic powder granules 6. The method for manufacturing the rare earth magnet 1 includes a (C) insulating layer formation step in which an insulating layer is formed on the magnetic powder granules 6 to obtain the magnetic powder granules 6, an (E) primary molding step in which the magnetic powder granules 6 is primary molded to obtain a primary molded body 14, and a (F) hot plastic deformation step in which the primary molded body 14 is hot plastically worked to obtain the rare earth magnet 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to magnetic powder particles that are a material for rare earth magnets, a method for producing the magnetic powder particles, and a method for producing a rare earth magnet that manufactures a rare earth magnet from the magnetic powder particles.

Background Art

[0002] In recent years, efforts toward realizing a low-carbon society or a decarbonized society have intensified, and research and development related to electrification technologies are being carried out in vehicles as well to reduce CO₂ emissions and improve energy efficiency. One of the methods for improving energy efficiency is to improve the efficiency of motors used as power sources. To improve motor efficiency, rare earth magnets have been widely used in recent years. And it is required to improve the magnetic properties of rare earth magnets. Since rare earth magnets are metallic magnets with low electrical resistivity, they have the problem that eddy current loss tends to increase. Accordingly, there is a technology for reducing overcurrent loss in rare earth magnets.

[0003] Patent Document 1 discloses a rare earth magnet capable of reducing eddy current loss, which has rare earth magnet powder covered with a film-like coating layer containing a rare earth oxide. Between the particles of the magnet powder in the state of being coated with the rare earth oxide, a binding portion containing rare earth oxide particles is interposed. The rare earth magnet is produced by subjecting a mixture of the rare earth magnet powder coated with the rare earth oxide and the rare earth oxide to high-temperature pressure molding.

[0004] Patent Document 2 describes, for the purpose of increasing the electrical resistivity of rare earth magnets, Nd2Fe 14 Disclosed is a method for producing a rare earth magnet, in which magnet powder made of an alloy mainly composed of a B compound is mixed with one or two or more insulating compounds selected from oxides such as CaO, nitrides such as BN, or fluorides such as CaF₂, and the mixture is subjected to hot plastic working to obtain a magnet material having anisotropy.

[0005] Patent Document 3 discloses a first method for manufacturing rare earth magnets, comprising the steps of: preparing isotropic quenched powder such as Nd-Fe-B magnet powder; mixing the isotropic quenched powder with a predetermined compound that will form an insulating layer; cold forming (pre-forming) the mixture; hot forming (densifying) the cold-formed body; and hot plastic working (anisotropizing). It is stated that the magnets manufactured by this method have a structure in which Nd-Fe-B quenched powder with a long side of 100 to 400 μm and a thickness of 20 to 40 μm is generally stacked on top of each other via compound powder. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Patent No. 4784173 [Patent Document 2] Japanese Patent Publication No. 2003-22905 [Patent Document 2] Japanese Patent Publication No. 2010-27852 [Overview of the project] [Problems that the invention aims to solve]

[0007] The rare earth magnet described in Patent Document 1 uses an insulator made of dysprosium oxide (Dy2O3) as the rare earth oxide. Since dysprosium oxide is hygroscopic, the magnetic properties of the rare earth magnet may be reduced by water adsorbed on the dysprosium oxide. In the method for manufacturing a rare earth magnet described in Patent Document 2, in the mixing step in which Nd-Fe-B magnet powder and an insulating compound are mixed, the magnet powder is pulverized and excessively subdivided, increasing the specific surface area of ​​the magnet powder and making it more susceptible to oxidation. As a result, the rare earth magnet may be oxidized, which may reduce the magnetic flux density of the rare earth magnet.

[0008] In the rare earth magnet manufacturing method described in Patent Document 3, compound A, which is at least one selected from the group consisting of fluorides, oxides, and inorganic salts of heavy rare earth elements, and compound B, which is a hydride of an alkaline earth metal, are reacted during the hot forming and heat treatment processes. However, side reactions such as oxidation of the magnet or improper reaction between compound A and compound B may reduce the magnetic properties of the manufactured rare earth magnet. Therefore, there is a need for rare earth magnet materials with reduced overcurrent loss, and for rare earth magnets with reduced overcurrent loss.

[0009] In view of the above background, the present invention aims to provide magnetic powders and granules that can be used as materials for rare earth magnets with reduced overcurrent loss, a method for manufacturing magnetic powders and granules, and a method for manufacturing rare earth magnets from magnetic powders and granules, thereby contributing to the improvement of energy efficiency. [Means for solving the problem]

[0010] To solve the above problems, one aspect of the present invention provides a magnetic powder material for a rare earth magnet, comprising a plurality of stacked, scale-like rare earth magnetic powders and an insulating layer provided on the surface, wherein the insulating layer contains a plurality of fluoride nanoparticles having a particle size of 1 to 100 nm, and the fluoride is an alkali metal fluoride or an alkaline earth metal fluoride.

[0011] According to this embodiment, it is possible to provide magnetic powders that can be used as materials for rare earth magnets, with reduced overcurrent loss.

[0012] To solve the above problems, one aspect of the present invention is a method for producing magnetic powders, comprising: a binding step of binding a plurality of rare earth magnetic powders in layers to obtain a magnetic powder precursor containing a plurality of stacked rare earth magnetic powders; and an insulating layer forming step of spraying a nanoparticle dispersion in which a plurality of fluoride nanoparticles are dispersed onto a plurality of magnetic powder precursors that are rolling and flowing to obtain the magnetic powders.

[0013] According to this aspect, it becomes easy to produce magnetic powder particles.

[0014] In order to solve the above problems, one aspect of the present invention is a method for producing a rare earth magnet that produces a rare earth magnet from magnetic powder particles, the method including: a primary forming step of arranging a plurality of the magnetic powder particles in a layered form to obtain a primary formed body in which the plurality of magnetic powder particles are primarily formed; and a hot plastic working step of subjecting the primary formed body obtained in the primary forming step to hot plastic working to obtain the rare earth magnet.

[0015] According to this aspect, it becomes easy to produce a rare earth magnet with reduced overcurrent loss. [Effects of the Invention]

[0016] According to the above aspects, it is possible to provide magnetic powder particles that serve as a material for a rare earth magnet with reduced overcurrent loss, a method for producing the magnetic powder particles, and a method for producing a rare earth magnet that produces a rare earth magnet from the magnetic powder particles. [Brief Description of the Drawings]

[0017] [Figure 1] Schematic cross-sectional view of the rare earth magnet according to the embodiment [Figure 2] Schematic cross-sectional view of the magnetic powder particles according to the embodiment [Figure 3] Diagram showing the method for producing a rare earth magnet according to the embodiment [Figure 4] Schematic diagram of a tumbling flow apparatus [Figure 5] Diagram showing differences in insulating layers depending on the proportion (wt%) of the binder compound contained in the insulating layers [Figure 6] Diagram showing differences in insulating layers depending on the difference in weight-average molecular weight of the binder compound contained in the insulating layers [Mode for Carrying Out the Invention]

[0018] Hereinafter, an embodiment of the rare earth magnet 1 of the present invention will be described in detail with reference to the drawings. In the following description, the numerical range indicated by "XX to XX" means "not less than XX and not more than XX" unless otherwise specified.

[0019] <Structure of Rare Earth Magnet 1> Figure 1 is a schematic cross-sectional view of the rare earth magnet 1 of the embodiment. As shown in Figure 1, the rare earth magnet 1 includes a plurality of insulated magnet powder particles 2 arranged in layers. The insulated magnet powder particle 2 has a plurality of laminated scaly (flake-shaped) rare earth magnet powders 3, and an insulating layer 4 formed on the surface layer of the insulated magnet powder particle 2 and having insulating properties. The insulating layer 4 covers the outer peripheral surfaces of the laminated rare earth magnet powders 3.

[0020] The rare earth magnet powder 3 is preferably a scaly neodymium magnet (Nd-Fe-B based magnet, specifically Nd2Fe 14 B).

[0021] The insulating layer 4 includes a plurality of fluoride nanoparticles 4A made of fluoride, which are particles made of calcium fluoride (CaF2). Calcium fluoride (CaF2) has a melting point higher than that of the rare earth magnet powder 3, and has low reactivity with the rare earth magnet powder 3. The particle size of the fluoride nanoparticles 4A is preferably 1 to 100 nm.

[0022] The fluoride nanoparticles 4A may be particles made of an insulating inorganic fluorine compound. The fluoride nanoparticles 4A preferably have a melting point higher than that of the rare earth magnet powder 3 and exhibit poor reactivity with the rare earth magnet powder 3. Because the melting point is higher than that of the rare earth magnet powder 3 and the reactivity with the rare earth magnet powder 3 is poor, the fluoride nanoparticles 4A are preferably nanoparticles made of alkali metal fluorides such as lithium fluoride, or nanoparticles made of alkaline earth metal fluorides such as magnesium fluoride, barium fluoride, or strontium fluoride. The insulating layer 4 may also contain, as fluoride nanoparticles 4A, a plurality of nanoparticles made of alkali metal fluorides and a plurality of nanoparticles made of alkaline earth metal fluorides. Furthermore, the insulating layer 4 may also contain nanoparticles containing alkali metal fluorides and alkaline earth metal fluorides as fluoride nanoparticles 4A.

[0023] As described later, during the manufacturing process of the rare earth magnet 1 (Figure 3 (F) Hot Plastic Working Process), the rare earth magnet powder 3 is heated while being pressurized in a direction perpendicular to the main surface (first direction). As a result, the crystal grains in the magnet are shorter in the first direction (compression direction) and longer in the orthogonal direction perpendicular to the first direction (direction in which the main surface extends). In addition, the rare earth magnet 1 is magnetized in the first direction (compression direction). The orientation of the crystal grains of the rare earth magnet 1 as described above, and the magnetization as described above, increases the squareness ratio of the rare earth magnet 1.

[0024] Furthermore, as shown in Figure 1, the rare earth magnet 1 is an aggregate of insulating magnet powders 2 having an insulating layer 4 on its surface. The rare earth magnet 1 has a high electrical resistivity because it consists of multiple insulating magnet powders 2 isolated from each other by the insulating layer 4. This reduces the overcurrent loss of the rare earth magnet 1. Therefore, the rare earth magnet 1 has a suitable square aspect ratio and can reduce the overcurrent loss of the rare earth magnet 1.

[0025] <Structure of magnetic powder 6> Figure 2 is a schematic cross-sectional view of the magnetic powder granules 6 of the embodiment. The magnetic powder granules 6 is the material for the rare earth magnet 1. As shown in Figure 2, the magnetic powder granules 6 includes a plurality of stacked, flaky rare earth magnetic powders 7, a binder compound layer 8 that binds the rare earth magnetic powders 7 together, and an insulating layer 9 having insulating properties provided on the surface.

[0026] The composition of rare earth magnetic powder 7 is the same as that of rare earth magnet powder 3. Rare earth magnetic powder 7 is a flaky rare earth magnet. The lower limit of the major axis of rare earth magnetic powder 7 is 300 μm. The average thickness of rare earth magnetic powder 7 is 10 μm to 30 μm. Rare earth magnetic powder 7 is a flaky neodymium magnet (Nd-Fe-B type magnet, more precisely Nd2Fe 14 B) is preferable. The rare earth magnetic powder 7 is anisotropic, but may also be isotropic. Anisotropy is the property that the crystal orientations (easy magnetization axis, c-axis) are aligned in a specific direction. Isotropy is the property that the crystal orientations are not aligned in a specific direction.

[0027] The binder compound layer 8 is located between adjacent rare-earth magnetic powders 7 and binds them together. The binder compound layer 8 consists of a binder compound. The binder compound is an acrylic polymer with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer is thermally decomposable, decomposing at a temperature lower than the melting point of the rare-earth magnetic powders 7.

[0028] The binder compound can be any compound capable of binding the rare earth magnetic powder 7. The binder compound has a weight-average molecular weight greater than 100,000, but does not necessarily have to be 300,000 or less. Furthermore, the binder compound does not have to be an acrylic polymer. The binder compound should preferably be a resin.

[0029] The insulating layer 9 contains a binder compound and a plurality of fluoride nanoparticles 4A made of fluoride. The fluoride nanoparticles 4A are particles made of calcium fluoride (CaF2) with a particle size of 1 to 100 nm. As described above, the fluoride nanoparticles 4A may be any particles made of an inorganic fluorine compound having insulating properties. The fluoride nanoparticles 4A preferably have a melting point higher than the melting point of the rare earth magnet powder 3 and have poor reactivity with the rare earth magnet powder 3. The fluoride nanoparticles 4A are preferably nanoparticles made of alkali metal fluorides such as lithium fluoride, or nanoparticles made of alkaline earth metal fluorides such as magnesium fluoride, barium fluoride, or strontium fluoride. The insulating layer 4 may also contain a plurality of nanoparticles made of alkali metal fluorides and a plurality of nanoparticles made of alkaline earth metal fluorides as the fluoride nanoparticles 4A. Furthermore, the insulating layer 4 may also include nanoparticles containing alkali metal fluorides and alkaline earth metal fluorides as fluoride nanoparticles 4A.

[0030] <Method for manufacturing rare earth magnet 1> Figure 3 is a diagram showing a method for manufacturing a rare earth magnet 1. As shown in Figure 3, the method for manufacturing a rare earth magnet 1 includes (A) a magnetic powder manufacturing step for manufacturing rare earth magnetic powder 7, (B) a binding step for obtaining a magnetic powder precursor 11 by binding the rare earth magnetic powder 7 in layers, (C) an insulating layer formation step for obtaining magnetic powder 6 by forming an insulating layer 9 on the magnetic powder precursor 11, (D) a binder removal step for obtaining degreased magnetic powder 13 by removing binder compounds contained in the magnetic powder 6 by thermal decomposition, (E) a primary molding step for obtaining a primary molded body 14 by primary molding of the degreased magnetic powder 13, and (F) a hot plastic deformation step for obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 14.

[0031] (A) The magnetic powder manufacturing process is a process for manufacturing rare earth magnetic powder 7 in the form of flakes of a predetermined size. (A) The melt spinning method is preferably used in the magnetic powder manufacturing process. As shown in Figure 3(A), the melt spinning method is a method for obtaining thin plate-shaped magnets by spraying rare earth magnets, which have been heated to a liquid state, onto a roll and then cooling it. The composition of the rare earth magnets to be liquefied is the same as the composition of the rare earth magnet powder 3. Furthermore, the thin plate-shaped magnets are crushed to obtain minute magnet fragments 16. Then, the rare earth magnetic powder 7 is classified from the minute magnet fragments 16 to obtain the rare earth magnetic powder 7. Note that the melt spinning method is not required in the magnetic powder manufacturing process. (A) The magnetic powder manufacturing process may also be a process for obtaining rare earth magnetic powder 7 by crushing thin plate-shaped rare earth magnets.

[0032] The rare earth magnetic powder 7 becomes more brittle as its thickness decreases. The lower limit of the major axis of the rare earth magnetic powder 7 is 300 μm, and the average thickness of the rare earth magnetic powder 7 is 10 μm to 30 μm. Furthermore, an average thickness of 20 μm is preferable for the rare earth magnetic powder 7.

[0033] The rare earth magnetic powder 7 is flaky and has a pair of main surfaces 7A. The main surface 7A is the largest of a pair of flat surfaces facing opposite directions. The rare earth magnetic powder 7 may have an aspect ratio of approximately 1 (for example, 0.7 to 1.0) when viewed from a direction perpendicular to the main surface 7A. The aspect ratio is the size of the minor axis b (minor axis diameter) relative to the major axis a (major axis diameter) of the particle (aspect ratio = minor axis b / major axis a). Here, the major axis a (major axis diameter) means the maximum Ferret diameter, and the minor axis b (minor axis diameter) means the minimum Ferret diameter. The measurement method for the major and minor axes conforms to the provisions of JIS Z8890:2017 "Evaluation of Particle Special Properties of Powders".

[0034] (B) The binding step is a step to obtain a magnetic powder precursor 11 by binding multiple rare earth magnetic powders 7 in layers with a binder compound. (B) In the binding step, a rolling flow device 20 (see Figure 4) may be used to spray a binder compound solution onto the rolling rare earth magnetic powders 7, thereby binding multiple rare earth magnetic powders 7 in layers with the binder compound.

[0035] The binder compound solution is, for example, a solution containing 4 wt% of the binder compound. The solvent of the binder compound solution is preferably 2-propanol (also called "isopropyl alcohol" or "IPA"). The solvent of the binder compound solution does not have to be 2-propanol. The solvent of the binder compound solution is preferably an alcohol. To allow for easy evaporation after the rare earth magnetic powder 7 has been bonded in layers, the solvent of the binder compound solution is preferably a solvent that evaporates easily at room temperature.

[0036] Figure 4 is a schematic diagram of the rolling fluidizer 20. As shown in Figure 4, the rolling fluidizer 20 comprises a main body case 22 having a fluidized bed 21 inside for rolling and fluidizing rare earth magnetic powder 7, a rotatable blade rotor 23 defining the bottom of the fluidized bed 21, a spray nozzle 24 provided on the side of the main body case 22, and a blower (not shown) that sends a swirling flow of air into the fluidized bed 21 through the gap between the outer circumference of the blade rotor 23 and the main body case 22. The blade rotor 23 has a conical portion 23A that protrudes upward in the center and stirring blades 23B that protrude upward and extend radially. The spray nozzle 24 is attached to the main body case 22 so that it can spray a binder compound solution toward the bottom of the fluidized bed 21.

[0037] (B) In the binding process, the rare earth magnetic powder 7 is placed in the fluidized bed 21. The blade rotor 23 is rotated, and a swirling flow of air in the fluidized bed 21 is generated by the blower. This causes the rare earth magnetic powder 7 in the fluidized bed 21 to tumble and flow. In this state, the binder compound solution is sprayed onto the tumbled rare earth magnetic powder 7 from the spray nozzle 24. Here, in order to properly bind the rare earth magnetic powder 7, it is preferable that the binder compound solution be sprayed at a rate of 5 g / min to 30 g / min per 1 kg of tumbled rare earth magnetic powder 7.

[0038] The rare earth magnetic powder 7 is bound by a sprayed binder compound solution. Here, the binder compound solution binds between the main surfaces 7A of adjacent rare earth magnetic powders 7. The solvent (IPA) evaporates from the binder compound solution binding the rare earth magnetic powders 7. Then, a magnetic powder precursor 11 is obtained, in which multiple rare earth magnetic powders 7 are bound in layers by the binder compound. Here, binding in layers means that multiple rare earth magnetic powders 7 are bound with their main surfaces 7A facing the same direction. The magnetic powder precursor 11 is a stack of scale-like rare earth magnetic powders 7. "Stacked scale-like rare earth magnetic powders 7" means multiple rare earth magnetic powders 7 that are stacked with their main surfaces 7A facing the same direction.

[0039] In the magnetic powder precursor 11, the binder compound solution that binds the rare earth magnetic powder 7 is dry. The magnetic powder precursor 11 preferably contains 0.5 to 2.5 wt% of the binder compound. The concentration of the binder compound in the binder compound solution and the amount of the binder compound solution injected are set so that the magnetic powder precursor 11 contains 0.5 to 2.5 wt% of the binder compound. In order for the rare earth magnet 1 produced from the magnetic powder precursor 11 to have suitable magnetic properties, the thickness of the magnetic powder precursor 11 in the stacking direction is preferably 0.15 mm or more and 1 mm or less.

[0040] As shown in Figure 3, (C) Insulating layer formation step is a step of forming an insulating layer 9 having insulating properties on the surface of the magnetic powder precursor 11 to obtain magnetic powder 6. Magnetic powder 6 is a powder obtained by forming an insulating layer 9 on the magnetic powder precursor 11. In (C) Insulating layer formation step, a nanoparticle dispersion liquid containing a plurality of fluoride nanoparticles 4A is sprayed onto the magnetic powder precursor 11, which is being rolled and flowed using a rolling flow device 20, to form an insulating layer 9 on the surface of the magnetic powder precursor 11. As described above, the fluoride nanoparticles 4A in this embodiment consist of calcium fluoride (CaF2) and are nanoparticles with a particle size of 1 to 100 nm.

[0041] The nanoparticle dispersion contains, for example, 4 wt% of fluoride nanoparticles 4A and 2.5 wt% of a binder compound. As a result, the insulating layer 9 formed when the nanoparticle dispersion dries contains 38 wt% of the binder compound and 62 wt% of fluoride nanoparticles 4A.

[0042] The solvent for the nanoparticle dispersion is preferably 2-propanol (IPA). The binder compound is a compound that can bind the fluoride nanoparticles 4A, and is preferably the same compound as the binder compound used in the binding step (B). The fluoride nanoparticles 4A are dispersed in the nanoparticle dispersion. The concentration of fluoride nanoparticles 4A, the concentration of the binder compound, and the solvent in the nanoparticle dispersion may be changed.

[0043] (C) In the insulating layer formation process, as shown in Figure 4, the magnetic powder precursor 11 is placed in the fluidized bed 21 of the rolling fluidizer 20. The blade rotor 23 is rotated and a swirling flow of air in the fluidized bed 21 is generated by the blower. As a result, the magnetic powder precursor 11 in the fluidized bed 21 rolls and flows. In this state, a nanoparticle dispersion is sprayed onto the rolling magnetic powder precursor 11 from the spray nozzle 24. The sprayed nanoparticle dispersion adheres to the surface of the magnetic powder precursor 11 and dries. As a result, an insulating layer 9 is formed on the surface of the magnetic powder precursor 11, and magnetic powder 6 is obtained.

[0044] The insulating layer 9 formed as described above preferably contains a plurality of fluoride nanoparticles 4A having a particle size of 1 to 100 nm and a binder compound that binds the plurality of fluoride nanoparticles 4A together in an amount of 20 wt% or more.

[0045] (D) The binder removal step is a step in which the magnetic powder 6 is heated to a temperature above the thermal decomposition temperature of the binder compound, causing the binder compound to decompose thermally and obtaining degreased magnetic powder 13 by removing the binder compound from the magnetic powder 6.

[0046] (D) In ​​the binder removal step, the magnetic powder 6 may be heated in the mold of the hot press machine. As shown in Figure 3(D), the mold 30 of the hot press machine has a cylindrical mold body 31 and an upper mold 32 and a lower mold 33 that can apply a compressive force in a first direction to the object inside the mold body 31. In Figure 3, the first direction is the vertical direction, but the first direction may be a direction other than the vertical direction.

[0047] (D) In ​​the binder removal process, the magnetic powder 6 placed in the mold body 31 of the mold 30 is heated to a temperature above the thermal decomposition temperature of the binder compound (e.g., 300°C to 400°C) for a predetermined time (e.g., 2 to 4 hours) in a reduced pressure environment or in an inert gas stream, without being pressurized by the mold 30 (upper mold 32 and lower mold 33). The inert gas is a gas that has poor reactivity with the rare earth magnetic powder 7. The inert gas is preferably a noble gas, for example. The inert gas is preferably helium gas. Air may be used instead of the inert gas.

[0048] The products of the thermal decomposition of the binder compound are discharged from the mold 30. The binder compound is preferably an acrylic polymer (polymethyl methacrylate) with a weight-average molecular weight greater than 100,000 and less than or equal to 300,000. The acrylic polymer is thermally decomposed into the monomer methyl methacrylate. The decomposition products generated by the thermal decomposition of the binder compound volatilize and are discharged from the mold 30.

[0049] (D) When the magnetic powder 6 is heated under reduced pressure in the binder removal process, the mold body 31 (mold 30) is heated under reduced pressure. In this case, the decomposition products of the binder compound (for example, the monomer methyl methacrylate) become more volatile when placed under reduced pressure and are more easily discharged outside the mold body 31 (mold 30). In addition, the decomposition products of the binder compound are less likely to accumulate around the magnetic powder 6, and their reaction with the rare earth magnetic powder 7 and the resulting deterioration of the rare earth magnetic powder 7 are suppressed.

[0050] When heating magnetic powder 6 in an inert gas stream, the magnetic powder 6 is heated while the inert gas is flowed inside the mold body 31 (mold 30). This makes it easier for decomposition products of the binder compound (e.g., methyl methacrylate monomer) to be discharged outside the mold body 31 (mold 30) by the inert gas stream. In addition, the decomposition products of the binder compound are less likely to accumulate around the magnetic powder 6, and their reaction with the rare earth magnetic powder 7, which degrades the rare earth magnetic powder 7, is suppressed. It is preferable that the inert gas be heated to a temperature above the thermal decomposition temperature of the binder compound before being introduced into the mold 30. This promotes the thermal decomposition of the binder compound because it is heated by the inert gas.

[0051] (E) The primary molding step is a step of pressurizing a plurality of degreased magnetic powder particles 13 to obtain a primary molded body 14. (E) A mold 30 may be used in the primary molding step. (E) The primary molding step is a step of primary molding the degreased magnetic powder particles 13, from which the binder compound has been removed from the magnetic powder particles 6, to obtain a primary molded body 14. (E) The primary molding step may be considered as a type of step of arranging a plurality of magnetic powder particles 6 obtained in the (C) insulating layer formation step in layers to obtain a primary molded body 14 in which the plurality of magnetic powder particles 6 have been primary molded.

[0052] (E) The primary molding step may be a step in which the degreased magnetic powder granules 13 are heated to a predetermined temperature in a mold 30 and a predetermined pressure is applied for a predetermined time to perform hot press molding (primary molding). Here, hot press molding may be performed at a mold temperature of 600°C to 700°C, preferably around 640°C. When the degreased magnetic powder granules 13 are pressurized in the mold 30, the multiple degreased magnetic powder granules 13 are oriented so that the main surface 7A of the rare earth magnetic powder 7 contained in the degreased magnetic powder granules 13 faces a first direction, and are stacked on top of each other in a direction perpendicular to the main surface 7A (first direction). Therefore, by hot press molding, the multiple degreased magnetic powder granules 13 are compressed and deformed in a state where they are stacked on top of each other in a direction perpendicular to the main surface (main surface 7A of the rare earth magnetic powder 7) (first direction).

[0053] (F) The hot plastic deformation process is a process of obtaining a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 14 obtained in the (E) primary molding process. (F) In the hot plastic deformation process, the primary molded body 14 is heated and pressurized to a temperature at which some of the crystal grains of the rare earth magnetic powder 7 undergo a phase change to the liquid phase (the melting point of the rare earth magnetic powder 7, for example, around 850°C), thereby causing the primary molded body 14 to plastically deform.

[0054] (F) The hot plastic deformation process is performed in the secondary molding die 40. The secondary molding die 40 has an upper press mold 41 and a lower press mold 42 that are arranged opposite each other. The primary molded body 14 is placed in the secondary molding die 40 such that the multiple degreased magnetic powder particles 13 contained in the primary molded body 14 are pressed in a direction perpendicular to the main surface 7A (first direction). During the plastic deformation process of the primary molded body 14, the c-axis direction (easy magnetization direction) of the crystal grains of the rare earth magnetic powder 7 contained in the primary molded body 14 is oriented in a direction parallel to the first direction (compression direction), so that magnetic anisotropy (uniaxial anisotropy) is exhibited in the primary molded body 14 during the plastic deformation process. The rare earth magnetic powder 3 contained in the rare earth magnet 1 is formed when the rare earth magnetic powder 7 is plastically deformed and its crystal grains are oriented in the first direction (compression direction). The rare earth magnet 1 (see Figure 1) obtained in the hot composition processing process is magnetized in the direction in which this magnetic anisotropy manifests (first direction).

[0055] (F) In the hot plastic deformation process, the degreased magnetic powder granules 13 are heated while being pressurized in a direction perpendicular to the main surface of the degreased magnetic powder granules 13 (first direction). As a result, the crystal grains in the magnet are shorter in the first direction (compression direction) and longer in the orthogonal direction perpendicular to the first direction (direction in which the main surface extends). In addition, the rare earth magnet 1 is magnetized in the first direction (compression direction). The crystal grains of the rare earth magnet 1 are oriented as described above, and the magnetization is performed as described above, thereby increasing the squareness ratio of the rare earth magnet 1.

[0056] Furthermore, as shown in Figure 1, the rare earth magnet 1 is an aggregate of insulating magnet powders 2 having an insulating layer 4 on its surface, and the insulating layer 4 increases its electrical resistivity. This reduces the overcurrent loss of the rare earth magnet 1. Therefore, the rare earth magnet 1 has a suitable square aspect ratio and can reduce the overcurrent loss of the rare earth magnet 1.

[0057] Next, the effects of the rare earth magnet 1 manufactured in this manner and its manufacturing method will be explained.

[0058] The magnetic powder material 6 comprises a plurality of stacked, flaky rare earth magnetic powders 7 and an insulating layer 9 provided on the surface. The insulating layer 9 contains a plurality of fluoride nanoparticles 4A having a particle size of 1 to 100 nm, and the fluoride contained in the fluoride nanoparticles 4A is alkali metal fluoride or alkaline earth metal fluoride.

[0059] Alkali metal fluorides and alkaline earth metal fluorides generally have poor reactivity with rare earth magnet powder 3. This suppresses the reaction between the insulating layer 9 and the rare earth magnet 1 (rare earth magnetic powder 7), thereby preventing the deterioration of the magnetic powder granules 6. Furthermore, in the process of manufacturing the rare earth magnet 1 from the magnetic powder granules 6, the insulating layer 9 protects the rare earth magnetic powder 7, thus suppressing the deterioration of the rare earth magnetic powder 7.

[0060] Furthermore, the particle size of the fluoride nanoparticles 4A is 1 to 100 nm, and the insulating layer 9 contains multiple fluoride nanoparticles 4A. As a result, the insulating layer 9 can be easily deformed by the flow of the fluoride nanoparticles 4A within the insulating layer 9. For example, when the insulating layer 9 is compressed, it can be easily stretched. This prevents the insulating layer 9 from rupturing and prevents electrical conduction between adjacent magnetic powder particles 6, thus ensuring that the insulating layer 9 reliably increases the electrical resistivity of the rare earth magnet 1 manufactured from the magnetic powder particles 6. Therefore, it is possible to provide magnetic powder particles 6 that can be used as a material for rare earth magnets with reduced overcurrent loss.

[0061] The insulating layer 9 contains 20 wt% or more of a binder compound that binds the fluoride nanoparticles 4A. Figure 5 shows the differences in the insulating layer 9 depending on the percentage (wt%) of the binder compound contained in the insulating layer 9. Figure 5(A) is an electron microscope image (SEM) of the insulating layer 9 when it does not contain a binder compound. Figure 5(B) is an electron microscope image (SEM) of the insulating layer 9 when it contains 20 wt% of the binder compound. Figure 5(C) is an electron microscope image (SEM) of the insulating layer 9 when it contains 38 wt% of the binder compound.

[0062] As shown in Figure 5(A), if the insulating layer 9 does not contain a binder compound, the thickness of the insulating layer 9 will be uneven and insufficient. Therefore, it is undesirable for the insulating layer 9 to not contain a binder compound. As shown in Figure 5(B), if 20 wt% of the binder compound is included, the insulating layer 9 will have sufficient thickness and the thickness unevenness will be sufficiently small. Therefore, it is preferable for the insulating layer 9 to contain 20 wt% of the binder compound. As shown in Figure 5(C), if 38 wt% of the binder compound is included, the insulating layer 9 will have sufficient thickness and the thickness unevenness will be sufficiently small. Therefore, it is preferable for the insulating layer 9 to contain 38 wt% of the binder compound. In short, by including 20 wt% or more of the binder compound in the insulating layer 9, the thickness unevenness will be sufficiently reduced and the insulating layer 9 will be more likely to have an appropriate thickness.

[0063] The weight-average molecular weight of the binder compound contained in the insulating layer 9 is between 100,000 and 300,000. Figure 6 shows the differences in the insulating layer 9 due to differences in the weight-average molecular weight of the binder compound contained in the insulating layer 9. Figure 6(A) is an electron microscope image (SEM) of the insulating layer 9 when it contains a binder compound with a weight-average molecular weight of 50,000. Figure 6(B) is an electron microscope image (SEM) of the insulating layer 9 when it contains a binder compound with a weight-average molecular weight of 100,000. Figure 6(C) is an electron microscope image (SEM) of the insulating layer 9 when it contains a binder compound with a weight-average molecular weight of 300,000 in both a nanoparticle dispersion and the insulating layer 9.

[0064] As shown in Figure 6(A), when the weight-average molecular weight of the binder compound is 50,000, the adhesive strength of the binder compound is weak, resulting in unevenness in the thickness of the insulating layer 9 and insufficient thickness of the insulating layer 9. Therefore, a binder compound with a weight-average molecular weight of 50,000 is undesirable. As shown in Figure 6(B), when the weight-average molecular weight of the binder compound is 100,000, the adhesive strength of the binder compound is sufficiently strong, resulting in sufficient thickness of the insulating layer 9 and significantly less unevenness in thickness. Therefore, a binder compound with a weight-average molecular weight of 100,000 is preferred. As shown in Figure 6(C), when the weight-average molecular weight of the binder compound is 300,000, the adhesive strength of the binder compound is sufficiently strong, resulting in sufficient thickness of the insulating layer 9 and significantly less unevenness in thickness. Therefore, a binder compound with a weight-average molecular weight of 300,000 is preferred.

[0065] As described above, when the weight-average molecular weight of the binder compound contained in the nanoparticle dispersion and the insulating layer 9 is between 100,000 and 300,000, the insulating layer 9 becomes less uneven and more likely to have an appropriate thickness.

[0066] The binder compound is thermally decomposable, meaning it decomposes at a temperature lower than the melting point of the rare-earth magnetic powder 7. This makes it easier to remove the binder compound from the magnetic powder 6 during the process of manufacturing the rare-earth magnet 1 from the magnetic powder 6.

[0067] The binder compound is an acrylic polymer. This makes it easier to remove the binder compound by thermal decomposition during the process of manufacturing the rare earth magnet 1 from the magnetic powder 6, and also makes it easier to thermally decompose the binder compound so that no residue remains.

[0068] The method for producing magnetic powder 6 includes (B) a binding step to obtain a magnetic powder precursor 11 containing a plurality of stacked rare earth magnetic powders 7, and an insulating layer 9 formation step to obtain magnetic powder 6 by spraying a nanoparticle dispersion liquid containing a plurality of fluoride nanoparticles 4A onto the plurality of magnetic powder precursors 11 that are being rolled and flowed. This makes it easier to produce magnetic powder 6.

[0069] A method for manufacturing a rare earth magnet from magnetic powder granules 6 includes (E) a primary molding step to obtain a primary molded body 14 in which multiple magnetic powder granules 6 are primary molded, and (F) a hot plastic deformation step to obtain a rare earth magnet 1 by performing hot plastic deformation on the primary molded body 14. This makes it easier to manufacture a rare earth magnet 1 with reduced overcurrent loss.

[0070] This concludes the description of specific embodiments, but the present invention is not limited to the above embodiments and can be broadly modified and implemented. For example, the solvent for the binder compound solution and the nanoparticle dispersion does not have to be IPA, but may be an alcohol that is liquid at room temperature, such as 1-propanol or butanol.

[0071] The above embodiments may also be described as follows:

[0072] One embodiment is a magnetic powder 6 which is the material for a rare earth magnet 1, comprising a plurality of stacked, flaky rare earth magnetic powders 7 and an insulating layer 9 provided on the surface of the magnetic powder 6, wherein the insulating layer 9 contains a plurality of fluoride nanoparticles 4A having a particle size of 1 to 100 nm, and the fluoride contained in the fluoride nanoparticles 4A is an alkali metal fluoride or an alkaline earth metal fluoride.

[0073] According to this embodiment, it is possible to provide magnetic powder granules 6 that serve as the material for a rare earth magnet 1, with reduced overcurrent loss.

[0074] In one embodiment, the insulating layer 9 contains 20 wt% or more of a binder compound that binds a plurality of fluoride nanoparticles 4A.

[0075] According to this embodiment, the insulating layer 9 is less uneven and is more likely to have an appropriate thickness.

[0076] In one embodiment, the weight-average molecular weight of the binder compound contained in the insulating layer 9 is between 100,000 and 300,000.

[0077] According to this embodiment, the insulating layer 9 becomes less uneven and more likely to have an appropriate thickness.

[0078] In one embodiment, the binder compound contained in the insulating layer 9 has thermal decomposition properties, meaning it decomposes at a temperature lower than the melting point of the rare earth magnetic powder 7.

[0079] According to this embodiment, in the process of manufacturing a rare earth magnet 1 from magnetic powder 6, it becomes easier to remove the binder compound from the magnetic powder 6.

[0080] In one embodiment, the magnetic powder 6 contains a binder compound that binds together a plurality of rare earth magnetic powders 7, and the binder compound is an acrylic polymer.

[0081] According to this embodiment, the binder compound can be easily removed by thermal decomposition during the process of manufacturing the rare earth magnet 1 from the magnetic powder granules 6, and the thermal decomposition of the binder compound can be easily carried out in a way that leaves no residual components.

[0082] One embodiment is a method for producing magnetic powder 6, comprising (B) a binding step of binding a plurality of rare earth magnetic powders 7 in layers to obtain a magnetic powder precursor 11 containing a plurality of stacked rare earth magnetic powders 7, and (C) an insulating layer forming step of spraying a nanoparticle dispersion liquid in which a plurality of fluoride nanoparticles 4A are dispersed onto the rolling magnetic powder precursor 11 to obtain magnetic powder 6.

[0083] According to this embodiment, it becomes easier to manufacture the magnetic powder granules 6.

[0084] One embodiment is a method for manufacturing a rare earth magnet 1, comprising: (E) a primary molding step in which a plurality of magnetic powders 6 are arranged in layers to obtain a primary molded body 14 in which the plurality of magnetic powders 6 are primary molded; and (F) a hot plastic deformation step in which the primary molded body 14 obtained in (E) a rare earth magnet 1 is obtained by performing hot plastic deformation on the primary molded body 14 obtained in the primary molding step.

[0085] According to this embodiment, it becomes easier to manufacture a rare earth magnet 1 with reduced overcurrent loss. [Explanation of Symbols]

[0086] 1: Rare earth magnets 4: Insulating layer 4A: Fluoride nanoparticles 6:Magnetic powder 7: Rare earth magnetic powder 9: Insulating layer 11: Magnetic powder precursor 14: Primary molded body

Claims

1. Magnetic powders and granules that are materials for rare earth magnets, Multiple layered, flaky rare earth magnetic powders, An insulating layer having insulating properties is provided on the surface, The insulating layer comprises a plurality of fluoride nanoparticles having a particle size of 1 to 100 nm, The fluoride is an alkali metal fluoride or an alkaline earth metal fluoride, and the material is a magnetic powder or granule.

2. The magnetic powder material according to claim 1, wherein the insulating layer contains 20 wt% or more of a binder compound that binds a plurality of fluoride nanoparticles.

3. The magnetic powder material according to claim 2, wherein the weight-average molecular weight of the binder compound is 100,000 or more and 300,000 or less.

4. The magnetic powder granules according to claim 2, wherein the binder compound has thermal decomposition properties, decomposing at a temperature lower than the melting point of the rare earth magnetic powder.

5. The magnetic powder material according to claim 2, wherein the binder compound is an acrylic polymer.

6. A method for producing magnetic powders according to any one of claims 1 to 5, A binding step to obtain a magnetic powder precursor containing a plurality of stacked rare earth magnetic powders by binding a plurality of the rare earth magnetic powders in layers, A method for producing magnetic powder, comprising: an insulating layer formation step of spraying a nanoparticle dispersion in which a plurality of fluoride nanoparticles are dispersed onto a plurality of magnetic powder precursors that are being rolled and flowed, in order to obtain the magnetic powder.

7. A method for producing a rare earth magnet from magnetic powder granules according to any one of claims 1 to 5, A primary molding step involves arranging a plurality of the magnetic powder particles in layers to obtain a primary molded body in which the plurality of magnetic powder particles are primary molded, A method for manufacturing a rare earth magnet, comprising: a hot plastic deformation step of performing hot plastic deformation on the primary molded body obtained in the primary molding step to obtain a rare earth magnet.

Citation Information

Patent Citations

  • High resistance rare earth magnet and its manufacturing method

    JP2003022905A

  • Method of manufacturing r-t-b based rare earth magnet

    JP2010027852A

  • Rare earth magnet and method for manufacturing the same

    JP4784173B2